A Longitudinal Functional Neuroimaging Study in Medication-Naïve Depression after Antidepressant Treatment - Tomioka, Hiroi; Yamagata, Bun; Kawasaki, Shingo; Pu, Shenghong; Iwanami, Akira; Hirano, Jinichi; Nakagome, Kazuyuki; Mimura, Masaru (PloS one, 2015)
Recent studies have indicated the potential clinical use of near infrared spectroscopy (NIRS) as a tool in assisting the diagnosis of major depressive disorder (MDD); however, it is still unclear whether NIRS signal changes during cognitive task are state- or trait-dependent, and whether NIRS could be a neural predictor of treatment response. Therefore, we conducted a longitudinal study to explore frontal haemodynamic changes following antidepressant treatment in medication-naïve MDD using 52-channel NIRS. This study included 25 medication-naïve individuals with MDD and 62 healthy controls (HC). We performed NIRS scans before and after antidepressant treatment and measured changes of [oxy-Hb] activation during a verbal fluency task (VFT) following treatment. Individuals with MDD showed significantly decreased [oxy-Hb] values during a VFT compared with HC in the bilateral frontal and temporal cortices at baseline. There were no [oxy-Hb] changes between pre- and post-antidepressant treatment time points in the MDD cohort despite significant improvement in depressive symptoms. There was a significant association between mean [oxy-Hb] values during a VFT at baseline and improvement in depressive symptoms following treatment in the bilateral inferior frontal and middle temporal gyri in MDD. These findings suggest that hypofrontality response to a VFT may represent a potential trait marker for depression rather than a state marker. Moreover, the correlation analysis indicates that the NIRS signals before the initiation of treatment may be a biological marker to predict patient's clinical response to antidepressant treatment. The present study provides further evidence to support a potential application of NIRS for the diagnosis and treatment of depression.